Facetas de mindfulness: características psicométricas de um instrumento de avaliação - Gregório, Sónia (2011)
Mindfulness has been defined as paying attention with purpose, in the present moment, and nonjudgmentally. Several measures of this construct have been developed. In this paper we propose to explore the underlying structure of the Portuguese version of the Five Facet Mindfulness Questionnaire (FFMQ). 821 individuals completed the FFMQ, as well as some other measures of psychopathology. The Exploratory Factor Analysis suggested a five-factor solution accounting for 50.48% of the variance after factor extraction. The facets were internally consistent and showed moderate positive correlations, except some unexpected negative correlations with the Observe and Non-judge facets. Most of the correlations between the five mindfulness facets and other psychological constructs resulted as expected, except for the facet Observe that behaved in a way not entirely consistent with the others. This study results shows the Portuguese version of the FFMQ as valid to the Portuguese population.